Arsenic Contamination of Ground Water and its Health Impact on Population of District of Nadia, West Bengal, India - Mazumder, Debendra Nath Guha (Medknow Publications, 2010)
BACKGROUND: The global health impact and disease burden due to chronic arsenic toxicity has not been well studied in West Bengal. OBJECTIVE: To ascertain these, a scientific epidemiological study was carried out in a district of the state. MATERIALS AND METHODS: Epidemiological study was carried out by house-to-house survey of arsenic affected villages in the district of Nadia. A stratified multi-stage design has been adopted for this survey for the selection of the participants. A total number of 2297 households of 37 arsenic affected villages in all the 17 blocks were surveyed in the district. RESULT: Out of 10469 participants examined, prevalence rate of arsenicosis was found to be 15.43%. Out of 0.84 million people suspected to be exposed to arsenic, 0.14 million people are estimated to be suffering from arsenicosis in the district. Highest level of arsenic in drinking water sources was found to be 1362 μg/l, and in 23% cases it was above 100 μg/l. Majority of the population living in the arsenic affected villages were of low socio-economic condition, inadequate education and were farmers or doing physical labour. Chronic lung disease was found in 207 (12.81%) subjects among cases and 69 (0.78%) in controls. Peripheral neuropathy was found in 257 (15.9%) cases and 136 (1.5%) controls. CONCLUSION: Large number of people in the district of Nadia are showing arsenical skin lesion. However, insufficient education, poverty, lack of awareness and ineffective health care support are major factors causing immense plight to severely arsenic affected people.